Angle expanding fracture analysis of Q420B angle steel. (November 2020) - Fu, Chunxia; Ren, Facai; Wang, Peng
Abstract: The cracking angle steel is analyzed by chemical composition analysis, tensile test, impact strength, bending test, metallographic structure and other physical and chemical test methods and all indicators meet the requirements of the standard, so material quality is not the cause of crack of angle steel. The stress distribution of Q420B angle steel in the process of expanding angle in cold working is analyzed by numerical simulation. Three dimensional simulation results show that when the angle of expansion reaches 92° and the maximum principal stress exceeds the tensile strength of the material, the angle steel breaks; The results of plane strain calculation show that when the angle of expansion reaches 92.6° and the maximum principal stress exceeds the tensile strength of the material, the angle steel breaks.